Cryptococcal meningitis and immune reconstitution inflammatory syndrome in a pediatric patient with HIV after switching to second line antiretroviral therapy: a case report - Otto, Ssegujja Boniface Joseph (BMC Infect Dis, 2020)
BACKGROUND: Cryptococcal meningitis (CCM) is a common and deadly disease among HIV-infected patients. Notable about CCM is its association with the immune reconstitution inflammatory syndrome (IRIS). Though it has been posited a switch from first to second-line antiretroviral therapy (ART) can induce CCM IRIS, a case presentation of CCM IRIS has not been published. CASE PRESENTATION: A 10-year-old, HIV-infected girl who initially presented with severe headache and new-onset seizures, with cerebrospinal fluid that returned antigen, India Ink, and culture positive for Cryptococcus neoformans. Notably, 8 weeks prior to seizures, she had switched from first line to second-line ART (abacavir-lamivudine-efavirenz to zidovudine-lamivudine-lopinavir/ritonavir) due to virologic failure, with a viral load of 224,000 copies/milliliter. At time of seizures and 8 weeks on second-line ART, her viral load had reduced to 262 copies/milliliter. Her hospital course was prolonged, as she had ongoing headaches and developed bilateral cranial nerve VI palsies despite clearance of Cryptococcus from cerebrospinal fluid on antifungal therapy and therapeutic lumbar punctures. However, symptoms stabilized, and she was discharged with oral fluconazole. Cranial nerve palsies resolved 10 weeks post discharge and she has remained disease free. CONCLUSIONS: We describe a case of CCM IRIS in a 10-year-old HIV infected child after changing to second-line ART. This case provides evidence that screening for cryptococcal antigenaemia prior to switch from first-line to second-line ART could be an important measure to prevent cryptococcal disease.